2021
DOI: 10.1039/d0nr07027k
|View full text |Cite
|
Sign up to set email alerts
|

Group-IV(A) Janus dichalcogenide monolayers and their interfaces straddle gigantic shear and in-plane piezoelectricity

Abstract: Inversion symmetry in 1T-phase of pristine dichalcogenide monolayer MX2 (M = Ge, Sn; X = S, Se) is broken in their Janus structures, MXY (M = Ge, Sn; X ≠...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 100 publications
5
82
0
3
Order By: Relevance
“…Our calculated results are good in agreement with the available data (0.73/ 1.51 eV at the PBE/HSE06 level), which were very recently reported by Nandi and co-workers. 31 This conrms that our computational method for electronic properties is valid. The calculated band structures of GeS 2 , GeO 2 , and GeSO monolayers are depicted in Fig.…”
Section: Electronic Propertiesmentioning
confidence: 86%
“…Our calculated results are good in agreement with the available data (0.73/ 1.51 eV at the PBE/HSE06 level), which were very recently reported by Nandi and co-workers. 31 This conrms that our computational method for electronic properties is valid. The calculated band structures of GeS 2 , GeO 2 , and GeSO monolayers are depicted in Fig.…”
Section: Electronic Propertiesmentioning
confidence: 86%
“…A series of Janus based on 2D structures have been investigated, from Janus dichalcogenides 27,28 to Janus monochalcogenides. 29–32 Along with that trend, Janus group IV chalcogenides, such as Ge 2 SSe, Sn 2 SeTe 33 or GeSSe and SnSSe 34 has also been studied very recently. It was found that many new physical properties were found in Janus structures due to the breaking of the mirror symmetry structure.…”
Section: Introductionmentioning
confidence: 92%
“…It was found that many new physical properties were found in Janus structures due to the breaking of the mirror symmetry structure. 30,34 In addition, the vertical asymmetry in the Janus structure also gave rise to an intrinsic built-in electric eld, which leads to difference in the vacuum levels between the two sides of the Janus monolayers. 31,35 In this study, we deal with the structural, mechanical, and electronic properties of Janus GeSnX 2 (X ¼ S, Se, Te) single-layers by mean of density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a large number of previous research on electrons and various excellent properties in 2D Janus materials [13][14][15][16][17][18][19][20][21][22][23]. Electric field and strain are considered as two effective ways to realize versatile physical properties in Janus XSn 2 Y monolayers [13].…”
Section: Introductionmentioning
confidence: 99%